A REVIEW OF TEACHING STRATEGIES FOR ENGLISH AS A FOREIGN LANGUAGE IN HEALTHCARE STUDIES (Zdravstveni glasnik, 2024)
Teachers of English as a foreign language are faced with difficulties in selecting the proper teaching strategy for students learning English for academic and professional purposes. Fifteen research studies were included in the current study on teaching strategies for students with English as a foreign language in healthcare studies. The objective is to determine the most useful and effective teaching strategies for healthcare students learning English as a foreign language. The review study was conducted using Noblit and Hare methasynthesis and Dearholt and Dang’s Johns Hopkins Nursing Evidence-Based Practice Model and Guidelines for evaluation, selection and analysis. Language teaching strategies play an important role in teaching English as a foreign language especially in specific professional environments such as healthcare and medicine. The study divides language teaching strategies for English in healthcare into two perspectives; those concerned with improving students’ language learning performance and those examining specific instruction strategies and their effects on students’ knowledge. Further it gives an outline of four general English language skills and most commonly used teaching strategies. The results of the study may be used by English language teachers and content creators for developing new teaching materials and courses to help students succeed. For healthcare as a profession, a future with newly educated professional who have skills in English and other foreign languages will be beneficial in helping their target population.